Information Literacy Among Undergraduate Students Of Health Services Administration In Ahvaz Jundishapur University Of Medical Sciences Based On SCONUL Seven Pillars Model: 2013 - Farzad Faraji Khiavi; Mansour Zahiri; Kambiz Ahmadi Angali; Bahareh Mirzaei; Mohammad Veisi; Marjan Arab Rahmatipour (Tehran University of Medical Sciences, 2014)
Background and Aim: Information literacy is a set of skills required to identify rightful information resources and access to them. These skills are empowering goal oriented use of information resources. This study aimed to determine the ability rate of information literacy among health services administration students in Jundishapur University of Medical Sciences based on SCONUL seven pillars model.   Materials and Methods: This cross-sectional descriptive-analytic study was conducted using a questionnaire developed based on SCONUL information literacy seven pillars model. Validity of the questionnaire was confirmed through content analysis and coefficient of Chronbach's alpha was 0.93. The study population included students of health services administration in Ahvaz Jundishapur University of Medical Sciences in 2013. The sample size included 40 cases collected randomly. Data analyzed through SPSS descriptive statistics and non-parametric statistical tests. Results: The mean score for the studied components of information literacy abilities among the study population was 0.5±0.43. Information Literacy score among freshmen was significantly different from other students (P<0.03). Students who passed Computer Basics and Research Methodology educational courses showed significant differences from other students in the information management (P<0.01). Conclusion: Given the increasing development in information technology, the need to develop information literacy skills is considerable especially among those who are going to be engaged in the health sector. Although studied students' information literacy estimated relatively well, it seems necessary to take measures to improve their information literacy in all components.